Advancements in herbal medicine-based nanozymes for biomedical applications - Mei Yang; Zhichao Deng; Yuanyuan Zhu; Chenxi Xu; Chenguang Ding; Yujie Zhang; Mingxin Zhang; Mingzhen Zhang; Ting Gao (Chinese Medical Journal)
Abstract. Nanozymes are a distinct category of nanomaterials that exhibit catalytic properties resembling those of enzymes such as peroxidase (POD), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). Nanozymes derived from Chinese herbal medicines exhibit the catalytic functions of their enzyme mimics, while retaining the specific medicinal properties of the herb (termed “herbzymes”). These nanozymes can be categorized into three main groups based on their method of synthesis: herb carbon dot nanozymes, polyphenol–metal nanozymes, and herb extract nanozymes. The reported catalytic activities of herbzymes include POD, SOD, CAT, and GPx. This review presents an overview of the catalytic activities and potential applications of nanozymes, introduces the novel concept of herbzymes, provides a comprehensive review of their classification and synthesis, and discusses recent advances in their biomedical applications. Furthermore, we also discuss the significance of research into herbzymes, including the primary challenges faced and future development directions.